Ein Haus für Herkules Das fürstliche Modellhaus der Residenzstadt Kassel - Architektur und Modellpraktiken im 18. und 19. Jahrhundert - Fitzner, Sebastian (Höfische Kultur interdisziplinär (HKI) - Schriften und Materialien des Rudolstädter Arbeitskreises zur Residenzkultur, 2021)
Dedicated to housing courtly architectural models, Landgrave Karl founded the so-called Modellhaus at the beginning of the 18th-century, an unusual building which went on to become one of the most admired sights of its time. The collection included, most importantly, a monumental model of the most famous of all the Kassel artworks, namely the statue of Hercules overlooking the extensive Karlsberg gardens. Through recently discovered plans, files, and contemporary travel memoirs, this book retraces the story of this unique building and its collection which lasted almost a century, guiding us through Berlin, Saint Petersburg, and Paris, to reveal the continuing importance of models.